Artificial Intelligence-Assisted Arabic Language Learning In Islamic Schools: Teachers’ Readiness, Challenges, And Pedagogical Opportunities - Mubarok Fatahillah; Husnul Hafidhoh (Syntax Corporation Indonesia, 2026)
This study investigates the potential of Artificial Intelligence (AI) to enhance Arabic language learning in madrasahs Al Falah. Using a mixed-methods approach, both qualitative and quantitative data were collected to examine the impact of AI on Arabic language education. The qualitative phase involved in-depth interviews, focus groups, and case studies with teachers, students, and administrators, exploring their perceptions, experiences, and challenges related to AI integration. The quantitative phase included a survey assessing attitudes towards AI in language learning. Results reveal that AI offers significant benefits, including personalized learning, real-time feedback, and improved student engagement. However, challenges such as lack of training, insufficient infrastructure, and funding limitations hinder its full implementation. The study concludes that while AI has the potential to revolutionize Arabic education in madrasahs Al Falah, its successful adoption requires addressing these challenges and providing proper support to educators.